Paddle grip : handgrip size ratio and associated factors contributing to the development of lateral elbow tendinosis and DeQuervains tenosynovitis in K1 marathon paddlers during the 2006 Berg River Canoe Marathon - Viviers, Wendy (Division of Physiotherapy, 2015)
Includes abstract.